2022
DOI: 10.3390/nu14194001
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Risk for COVID-19-Related Hospitalization in Adults Aged 50 and Older in Europe

Abstract: Higher body mass index (BMI) has been associated with a higher risk for severe COVID-19 outcomes. The aim of this study was to investigate associations among BMI, underlying health conditions and hospital admission as well as the effects of COVID-19 vaccines in adults aged 50 years and older in Europe using data from the Survey of Health, Ageing and Retirement in Europe (SHARE) which was collected from June to August 2021, shortly after the second wave of the COVID-19 pandemic occurred in Europe. Survey data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Interestingly, BMI, which has been felt to be a major risk factor both for SARS-CoV2 severity and transaminase elevation secondary to non-alcoholic steatohepatitis (NASH) or non-alcoholic fatty liver disease (NAFLD) 20,21 , was not relevant, displaying no increased risk of transaminase elevation. However, as our hospital center serves a patient population with atypical demographics (see high percentage of Black race in demographics) this may be an outlier reflecting a specific resistance to NASH/NAFLD due to polymorphisms such as PNPLA-3 or MBOAT7 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, BMI, which has been felt to be a major risk factor both for SARS-CoV2 severity and transaminase elevation secondary to non-alcoholic steatohepatitis (NASH) or non-alcoholic fatty liver disease (NAFLD) 20,21 , was not relevant, displaying no increased risk of transaminase elevation. However, as our hospital center serves a patient population with atypical demographics (see high percentage of Black race in demographics) this may be an outlier reflecting a specific resistance to NASH/NAFLD due to polymorphisms such as PNPLA-3 or MBOAT7 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity and diabetes are risk factors for increasing the severity of COVID-19. 31,32 In T2DM patients, obesity is associated with poor early prognosis in COVID-19 patients. Albahrani et al 33 prove that obesity was identified as an independent risk factor for the risk of decreased oxygen saturation in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to a meta-analysis of 3700 individuals, 14.4% of patients hospitalized for severe SARS-CoV-2 symptoms acquired diabetes. The patients with "new diabetes" were more likely to need urgent treatment than those who already had diabetes before contracting the virus [153,154]. Even three years after the pandemic, researchers are still unsure whether COVID-19 speeds up the development of diabetes, causes it, or does both.…”
Section: Diabetes and Covid-19mentioning
confidence: 99%